2003
DOI: 10.1186/bcr658
|View full text |Cite
|
Sign up to set email alerts
|

A combined analysis of outcome following breast cancer: differences in survival based on BRCA1/BRCA2 mutation status and administration of adjuvant treatment

Abstract: Background: The prognostic significance of germline mutations in BRCA1 and BRCA2 in women with breast cancer remains unclear. A combined analysis was performed to address this uncertainty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
193
5
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(220 citation statements)
references
References 41 publications
16
193
5
6
Order By: Relevance
“…This observation is substantiated by two earlier studies among Ashkenazi Jewish breast cancer patients. In these studies, BRCA1 status was a strong predictor of breast cancer survival only among women who did not receive chemotherapy, while among women who received chemotherapy it was not (Goffin et al, 2003;Robson et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This observation is substantiated by two earlier studies among Ashkenazi Jewish breast cancer patients. In these studies, BRCA1 status was a strong predictor of breast cancer survival only among women who did not receive chemotherapy, while among women who received chemotherapy it was not (Goffin et al, 2003;Robson et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…The risk of local recurrence does not appear to be higher among patients with a strong family history than among low familial risk patients, rendering high familial risk patients equally eligible for breast-conserving surgery (Eccles et al, 2001;Vlastos et al, 2002;Robson et al, 2004). However, their risk for contralateral disease is highly increased (Robson et al, 2004).…”
mentioning
confidence: 99%
“…25,34,35,[37][38][39][40][41] Between 73 and 90% of BRCA1 carcinomas were estrogen receptor-negative in different series. 34,35,38 For example, Lakhani et al 25 reported that 90% of BRCA1-related breast cancers were estrogen receptor-negative compared with 35% in controls.…”
Section: Familial Breast Cancer Characteristicsmentioning
confidence: 99%
“…Thus, estrogen receptor expression has been reported in around 65% of BRCA2 tumors. 25,38,39 Between 40 and 60% of BRCA2 carcinomas express progesterone receptor 25,38,39 ( Table 2).…”
Section: Familial Breast Cancer Characteristicsmentioning
confidence: 99%
“…On the other hand, BRCA2-associated breast carcinomas are rarely basal-like phenotype, also are of higher grade (usually grade 2/3) than sporadic age-matched controls [21], and tend to be ER and PR positive [23].…”
Section: Histological Characterization Of Basal-like Breast Cancersmentioning
confidence: 99%